Antibacterial Effect of Gallic Acid against Aeromonas hydrophila and Aeromonas sobria Through Damaging Membrane Integrity - Lu, Jing; Wang, Zhenning; Ren, Mengrou; Huang, Guoren; Fang, Baochen; Bu, Xiujuan; Liu, Yanhui; Guan, Shuang (Current Pharmaceutical Biotechnology, 2016)
In the study, we investigated the antibacterial activity and mechanism of gallic acid against Aeromonas hydrophila and Aeromonas sobria. Gallic acid showed strong antimicrobial activity against the two bacteria. Furthermore, the antibacterial mechanism of gallic acid (0, 3, 6, 12 mM) was performed by membrane integrity assay and scanning electron microscopy (SEM) assay. The results showed that gallic acid notably increased the released material absorption value at 260, 280 nm and electric conductivity in a dose-dependent manner. Moreover, the SEM assay showed that gallic acid induced severe shrink of bacterial intima and irregular morphology in a dose-dependent manner. The SDS-PAGE profiles further confirmed that gallic acid could damage bacterial cells. These results indicated gallic acid exhibited antibacterial effect by destroying membrane integrity of A. hydrophila and A. sobria. Hence, gallic acid has great potential as a new natural food preservative in food fresh-keeping and storage.
Keywords: antibacterial activity